Electricity Industrial Organization: What About The Strategic Behavior Of Hydro And Thermal Operators? - Hedfi, Houeida; Dakhlaoui, Ahlem (International Journal of Energy Economics and Policy, 2020)
In this paper, we develop a two-period model where we analyze and compare a hydro/thermal electrical system under different industrial organization: monopoly, Cournot competition and collusion; under storage constraint, water availability constraint and thermal turbine capacity constraint. First, we prove that the technological complementarity has an important role in satisfying electricity demand in the different industrial organizations. Second, we show by the analytical resolution, that intertemporal private monopoly water transfer from off-peak season to peak season is not as high as the same transfer under a public monopoly and therefore this increases the market price. Under Cournot competition, an increase in the peak season demand implies a water transfer strategy from off-peak to peak season. The results of collusion show that the electricity price is less dependent on the hydropower capacity. Keywords: Electricity market; Monopoly; Competition; Collusion; Hydro; Thermal. JEL Classifications: L20; Q40; Q25. DOI: https://doi.org/10.32479/ijeep.8775 <!--EndFragment-->